Comparison of the Effect of Nd:YAG Laser and Sandblasting on Shear Bond Strength of a Commercial Ni-Cr Alloy to Porcelain - Elnaz Moslehifard; Nasim Khosronejad; Farahnaz Fahimipour (Mashhad University of Medical Sciences, 2016)
Introduction: Failures might occur at metal‒porcelain interfaces as a problem with metal‒ceramic restorations even with the application of airborne-particle abrasion technique. This study was undertaken to evaluate the effect of Nd:YAG laser treatment on the bond strength of porcelain fused to metal. Methods:  Twenty-four cylindrical specimens (4 mm in diameter and 4 mm in height) were made of a commercially available nickel‒chromium alloy by lost-wax technique. Half of the specimens were surface-treated by air-borne particles and the other half was irradiated with Nd:YAG laser beams (wavelength of 1064 nm, energy and frequency of 120 mJ and 10 Hz, respectively, and a power setting of 6 kW). All the specimens (air-abraded and laser-treated) were covered with a 4-mm layer of opaque porcelain in two-stage baking and subjected to shear bond strength test (a 10-kgf at 1 mm/min) until fracture occurred. A fractured specimen from each group was evaluated using scanning electron microscopy. T-test was used for statistical analysis and statistical significance was set at P